Acceleration Independent Along-Track Velocity Estimation of Moving Targets - Baumgartner, S. V.; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2008)
In the paper a method for along-track velocity estimation of moving targets is presented. This method exploits the along-track interferometric (ATI) phase ramp of a range compressed moving target signal between two or more receiving channels. The slope of this phase ramp is mainly influenced by the along-track velocity but not by accelerations. Hence, acceleration independent along-track velocity estimation is feasible. A verification of the proposed method is performed by using both simulations and real two- and four-channel X-band data acquired with DLR′s E-SAR and F-SAR system.
DLR Import::2019-04-03